End-user quality characteristics and preferences for cassava, yam and banana products in rural and urban areas - a review - Osunbade, A.O.; Alamu, Emmanuel Oladeji; Awoyale, W.; Akinwande, B.; Adejuyitan, A.; Maziya-Dixon, Busie (Informa UK Limited, 2023)
The review attempted to evaluate the quality attributes and the preferred selected roots, tubers, and bananas (RTB) items (gari/eba, lafun, yam flour, pounded yam, boiled yam, and plantain flour) among the end-users in Nigeria’s rural, peri-urban, and urban segments. The results showed that depending on location, consumers’ preferred quality attributes of gari in the rural area are dry, bright/shiny, white, sweet, dense, fine, cooked aroma and sour/sweet gari. Cooked yam attributes include white or cream colour, soft, sticky to the touch, non-fibrous texture, easy chewing, crumbly/friable texture, sweet taste, and pleasant odor. Stretchy, moldable, non-sticky, smooth, moderately soft/hard, and pleasant aroma is a high-quality pounded yam. Plantains fingers of medium to large size, light yellow pulp, no black marks on the peel, firm texture, a medium intensity aroma and flavor, medium sweet fruits, and a shelf-life of 7–9 days under room temperature were preferred by consumers. Consumers also prefer plantain amala which is mouldable, smooth, and stretchable. This review provides preliminary details on consumer desired attributes of the selected RTB products in rural and urban areas with a shortage of data on the peri-urban consumer preference. Thus, detailed information on peri-urban consumer preferences should be studied further and correlated with the rural-urban consumer preferences for RTB products.